The Finite Element Method for Nonlinear Huxely Equation - Jabbar, Ahmed (University of Thi-Qar Journal of Science, 2010)
In this paper , we present a finite element method (F.E.M.) for solving the non-linear huxely equation by using Crank-Nicolson scheme with the predictor - corrector method. The numerical results and absolute errors showed that the Crank - Nicolson finite element method is more accurate and better than respectively from the numerical results and the absolute errors which that presented by Explicit and Crank-Nicolson finite difference method (F.D.M.) [7] .